New realities and conditions of organization of the educational process in higher education institutions in Ukraine - Vasetska, L. I.; Solovyova, O. V.; Васецька, Лариса Іванівна; Соловйова, Ольга Володимирівна (Запорізький національний університет, 2021)
The article is devoted to the problems of innovation in the modern paradigm of “blended learning”, which is developing in the Covid-19 pandemic. The article highlights the positive and negative aspects in the organization of blended learning. An analysis and interpretation of new components of the modern educational paradigm such as “student social skills”, “individual free educational trajectory”, “independent learning”, “innovative learning technology”, “IT-technology”, “learning platform” and other. The peculiarities of the organization of the educational process, which takes place in an online format in synchronous and asynchronous modes on the basis of MS TEAMS cloud services, are studied. The article identifies the effectiveness of blended learning based on the latest learning platforms. It is noted that the model of blended learning is focused on the active modernization of education and improving the quality of education through digital technologies, to meet the educational needs of students in accordance with their individual capabilities and abilities. Particular attention is paid to the choice of educational platform, optimal ways of organizing blended learning in free economic education, learning styles, analysis and qualification of methodological factors that create conditions for quality distance education. Effective methods of teaching and organization of the educational process are described, the question of methodological bases of transition from offline to online format of education is raised. The article highlights the problems that arise between educators and students during the online learning format. The definition of the term “modern high school teacher” is presented, the typical styles of learning, communication and management of a student group in the conditions of distance learning as a component of blended learning are listed. Criteria for the effectiveness of blended learning are studied and recommendations for improving the format of education are provided, as well as promising areas of research on methodological and organizational issues within the new paradigm of education. Стаття присвячена проблемам інновацій у сучасній парадигмі «змішане навчання», яке розвивається в умовах пандемії Covid-19. У статті висвітлені позитивні та негативні аспекти в організації змішаного навчання. Представлено аналіз і надано тлумачення нових компонентів сучасної освітньої парадигми таких, як «соціальні навички студента», «індивідуальна вільна освітня траєкторія», «самостійне учіння», «інноваційна технологія навчання», «IT-технології» «навчальна платформа» тощо. Досліджуються особливості організації навчального процесу, який відбувається в онлайн форматі у синхронному й асинхронному режимах на основі хмарних сервісів MS TEAMS. У статті визначаються чинники ефективності змішаного навчання на базі новітніх навчальних платформ. Зазначається, що модель змішаного навчання орієнтована на активну модернізацію освіти та підвищення якості освіти за допомогою цифрових технологій, на забезпечення освітніх потреб студентів відповідно до їхніх індивідуальних можливостей і здібностей. Особлива увага приділена питанням вибору навчальної платформи, оптимальних шляхів організації змішаного навчання у ЗВО, стилів навчання, аналізу та кваліфікації методичних чинників, які створюють умови для якісної дистанційної освіти. Описуються ефективні методи навчання й організації навчального процесу, піднімається питання методологічних основ переходу з офлайн до онлайн формату освіти. У статті актуалізуються проблеми, що виникають у освітян і у студентів під час онлайн формату навчання. Представлено визначення поняття «сучасний викладач вищої школи», перераховуються типові стилі навчання, спілкування і керування студентською групою в умовах дистанційного навчання, як компонента змішаного навчання. Досліджуються критерії результативності змішаного навчання і надаються рекомендації щодо вдосконалення формату освіти, а також окреслені перспективні напрямки дослідження з методичних та організаційних питань у межах нової парадигми освіти.
Нові реалії та нові умови організації навчального процесу в закладах вищої освіти України
Vasetska L. I. - orcid.org/0000-0001-6622-112X; Solovyova O. V. - orcid.org/0000-0001-7321-0525
Keywords: blended learning; educational paradigm; IT-technologies; learning platform; methods and forms of learning; styles; змішане навчання; IT-технології; методи і форми навчання; навчальна платформа; освітня парадигма; стилі